Flax Seed (Linum usitatissimum): the Healthy Medicinala and Preventive Food (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Flaxseeds have been known since ancient times to the Greeks and Pharaohs for being one of the most important types of medicinal seeds with many benefits for the body.Flaxseed is mainly considered as one of the oil crops that has gained great attention as a health food, as it has proven its effective role in the field of cardiovascular diseases, reducing  the proportion of fat and sugar in the blood, and as an anti-cancer of the breast and colon. Flaxseeds have also been shown to possess antioxidant and anti-inflammatory properties  in experimental studies in animals as well as humans. Researchers have reported that food products containing flaxseeds can have good consumer acceptance along with their nutritional benefits. This article highlights the effective role of flax seeds in the treatment or prevention of many diseases as a medicinal, preventive and curative food.